Implementation Of Coaching For Prisoners Who Abuse Narcotics As An Effort To Prevent Criminal Offenses (Case Study Of Class Ii Langkat Narcotics Correctional Institution) - Rudi Prasetyo Panjaitan; T. Riza. Zarzani (ASIAN PUBLISHER, 2023)
Implementation of Coaching of Narcotics Abuse Convicts as an Effort to Prevent Repetition of Crimes (Case Study of Class II Langkat Narcotics Correctional Institution. This study aims to determine the implementation of coaching conducted by the Class II Langkat Narcotics Correctional Institution against narcotics abuse inmates as an effort to prevent repetition of criminal acts and to determine the effectiveness of the implementation of inmate coaching at the Class II Langkat Narcotics Correctional Institution. This research was conducted at the Class II Langkat Narcotics Penitentiary. The data obtained then processed and analyzed descriptively qualitative that is where the data is collected, compiled, interpreted, and analyzed so as to provide a complete description in accordance with the problem at hand. The results showed that (1) Implementation of Coaching in Correctional Institution Narcotics Class II Langkat implemented in several stages including the initial stage, the advanced stage and the final stage. In the early stages include personality development and independence, in the advanced stage there is an assimilation stage where the inmate is entitled to leave before release or parole. at this stage also implemented social work assimilation which aims that if the inmate later has been released then he is not ostracized by the community and does not repeat the crime again. This final stage of coaching will be given parole for prisoners who have met the requirements. (2) The implementation of inmate coaching at the Class II Langkat Narcotics Penitentiary has been going well but has not been able to run effectively. This is because the implementation of coaching is not classified based on the crime, which means that the coaching carried out on narcotics and non-narcotics prisoners is equalized.